Farmer characteristics associated with improved and high farm business performance - Wilson, Paul (Institute of Agricultural Management, 2014)
Common Agricultural Policy reform, coupled with increasing market and climatic volatility will necessitate a competitive, resilient and environmentally sustainable UK agricultural industry reliant upon successful farm business management. Drawing upon in depth semi-structured interviews with 24 ‘high’ or ‘improved’ English farmers, results indicate that they typically hold agricultural qualifications, draw upon a range of information sources, recognise and draw upon farm-specific advantages, have low business debt, keep up to date with new industry developments and use a range of marketing channels. Additionally, these farmers seek to maximise profit within the context of farm and family objectives by focusing upon cost control, attention to detail, product quality and achieving high yields whilst primarily focusing upon enterprise margins; succession planning played an important role in decision making on some farms. Farmer decision making represents the outcome of responses to complex inter-linked issues; policy makers face the challenge of understanding this complexity and delivering policies that will generate multi-output objectives.